Effects of Ni and Zn on Growth of Vigna Mungo, Vigna Radiata and Glycine Max - ASHOK K,; B.S. BISHT,; MANISH K,; LALIT K, (International Journal of Pharma and Bio Sciences, 2010)
Heavy metals and other pollutants in the environment damage to the plants. Heavy metals include lead (Pb), cadmium (Cd), zinc (Zn), arsenic (As), nickel (Ni), chromium (Cr), copper (Co) etc. A pollutant is any substance in the environment, which causes objectionable effects, impairing the welfare of the environment, reducing the quality of plant life and may eventually cause plant death. Such a substance has to be present in the environment beyond a set or tolerance limit, which could be either a desirable or acceptable limit. Hence, environmental pollution is the presence of a pollutant in the environment viz. air, water and soil, which may be poisonous or toxic and cause harm to plants in the polluted environment. Increases of metal content ions when present at an elevated level in the environment are absorbed by roots of the plants and translocated to different plant parts, leading to impaired metabolism and reduced growth and Ni and Zn considered as essential micronutrients, increased concentration poses toxicity on metabolic and cytological activity of the plants. In the present investigation, the three plant of Indian pulses Vigna mungo, Vigna radiata and Glycine max which is the major pulses for farmer and all, were taken and the effect of different grade of Ni and Zn observed for the growth in pulses. The plant of one week and one month were taken for the present study. It was observed that the Ni and Zn had reduced cytological activity in the growing plant contrasting to control plants. They, thus reduce the plant growth in excess.